First-in-Human Experience With Peritoneal Direct Sodium Removal Using a Zero-Sodium Solution: A New Candidate Therapy for Volume Overload. Issue 13 (31st March 2020) - Rao, Veena S.; Turner, Jeffrey M.; Griffin, Matthew; Mahoney, Devin; Asher, Jennifer; Jeon, Sangchoon; Yoo, Peter S.; Boutagy, Nabil; Feher, Attila; Sinusas, Albert; Wilson, F. Perry; Finkelstein, Fredric; et al.
Abstract : Background: Loop diuretics have well-described toxicities, and loss of response to these agents is common. Alternative strategies are needed for the maintenance of euvolemia in heart failure (HF). Nonrenal removal of sodium directly across the peritoneal membrane (direct sodium removal [DSR]) with a sodium-free osmotic solution should result in extraction of large quantities of sodium with limited off-target solute removal. Methods: This article describes the preclinical development and first-in-human proof of concept for DSR. Sodium-free 10% dextrose was used as the DSR solution. Porcine experiments were conducted to investigate the optimal dwell time, safety, and scalability and to determine the effect of experimental heart failure. In the human study, participants with end-stage renal disease on peritoneal dialysis (PD) underwent randomization and crossover to either a 2-hour dwell with 1 L DSR solution or standard PD solution (Dianeal 4.25% dextrose, Baxter). The primary end point was completion of the 2-hour dwell without significant discomfort or adverse events, and the secondary end point was difference in sodium removal between DSR and standard PD solution. Results: Porcine experiments revealed that 1 L DSR solution removed 4.1±0.4 g sodium in 2 hours with negligible off-target solute removal and overall stable serum electrolytes. Increasing the volume of DSR solution cycled across the peritoneum increased sodium removal and substantially decreased plasma volume ( P =0.005). In the setting of experimental heart failure with elevated right atrial pressure, sodium removal was ≈4 times greater than in healthy animals ( P <0.001). In the human proof-of-concept study, DSR solution was well tolerated and not associated with significant discomfort or adverse events. Plasma electrolyte concentrations were stable, and off-target solute removal was negligible. Sodium removal was substantially higher with DSR (4.5±0.4 g) compared with standard PD solution (1.0±0.3 g; P <0.0001). Conclusions: DSR was well tolerated in both animals and human subjects and produced substantially greater sodium removal than standard PD solution. Additional research evaluating the use of DSR as a method to prevent and treat hypervolemia in heart failure is warranted. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03801226. Abstract : Supplemental Digital Content is available in the text.